1998
DOI: 10.1177/001872679805100105
|View full text |Cite
|
Sign up to set email alerts
|

Family-Responsive Variables and Retention-Relevant Outcomes Among Employed Parents

Abstract: This study examined the influence of family-responsive variables and the moderating influence of gender on the retention-relevant outcomes of organizational commitment and turnover intentions. Data were obtained with the aid of structured questionnaires from employed parents (N = 228) in a human service authority in Hong Kong. Results of regression analysis revealed that satisfaction with work schedule flexibility and supervisor work-family support were related to both retention-relevant outcomes. Contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 37 publications
5
71
0
5
Order By: Relevance
“…With regard to job attitudes, use of and satisfaction with work schedule flexibility has been associated with increased organizational commitment and reduced turnover intentions (Aryee, Luk, & Stone, 1998;Halpern, 2005;Houston & Waumsley, 2003), and voluntary reduced hours have been linked to greater job satisfaction, loyalty, and organizational commitment (Williams, Ford, Dohring, Lee, & MacDermid, 2000). A number of studies have found that employees who benefit from childcare centres, referral services and other family-supportive practices report higher levels of commitment to the organization (Goldberg, Greenberger, Koch-Jones, O'Neil, & Hamill, 1989;Grover & Crooker, 1995;Orthner & Pittman, 1986;Youngblood & Chambers-Cook, 1984).…”
Section: Improved Job-related Attitudes and Perceptions Of Organizatimentioning
confidence: 99%
“…With regard to job attitudes, use of and satisfaction with work schedule flexibility has been associated with increased organizational commitment and reduced turnover intentions (Aryee, Luk, & Stone, 1998;Halpern, 2005;Houston & Waumsley, 2003), and voluntary reduced hours have been linked to greater job satisfaction, loyalty, and organizational commitment (Williams, Ford, Dohring, Lee, & MacDermid, 2000). A number of studies have found that employees who benefit from childcare centres, referral services and other family-supportive practices report higher levels of commitment to the organization (Goldberg, Greenberger, Koch-Jones, O'Neil, & Hamill, 1989;Grover & Crooker, 1995;Orthner & Pittman, 1986;Youngblood & Chambers-Cook, 1984).…”
Section: Improved Job-related Attitudes and Perceptions Of Organizatimentioning
confidence: 99%
“…The construct of family-supportive supervision has been shown to have four dimensions: emotional support, instrumental support, role modeling, and creative work-family management (Hammer et al, 2009). Family-supportive supervision has been linked to reduces stress and strain (e.g., lower stress (Behson, 2005;Thompson & Prottas, 2006), emotional exhaustion (Thompson, Kirk, & Brown, 2005b), work-family conflict (Kossek et al, In press), cardiovascular risk factors (Berkman et al, 2010); and longer sleep (Berkman et al, 2010)) as well as improved organizational outcomes (e.g., greater job performance (Clark, 2001;, job satisfaction (Aryee & Luk, 1996;Behson, 2005;Frye & Breaugh, 2004;Hammer et al, 2009; and organizational commitment (Allen, 2001;Aryee et al, 1998;Thompson et al, 2004), and lower withdrawal behaviors (Allen, 2001;Aryee et al, 1998;Behson, 2005;Hammer et al, 2009;Thompson et al, 1999;Thompson et al, 2004)). The link between family-supportive supervision and these important employee and organizational outcomes demonstrated the importance of understanding the antecedents of family-supportive supervision and how it could be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Allen (2001) found that supervisor support was negatively related to work-family conflict and positively related to organizational commitment. Aryee, Luk, and Stone (1998) demonstrated that greater familysupportive supervision was related to increased organizational commitment. Thompson, Jahn, Kopelman, and Prottas (2004) also found that greater familysupportive supervision was associated with increased organizational commitment.…”
Section: Overview Of Family-supportive Supervision and Organizationalmentioning
confidence: 98%
See 2 more Smart Citations